Biomechanical Testing of an Upper-Extremity Occupational Exoskeleton - Preliminary Report on Methodologies and Pilot Data - Kudernatsch, Simon; Peterson, Donald R. (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2018)
Current and rapidly emerging occupational exoskeleton and exosuit technologies target increases in worker performance and safety through reductions of potentially harmful biomechanical exposures. While long-term effectiveness of these technologies cannot be readily evaluated, short-term effectiveness could be; however, the development of standardized assessment methods for exoskeleton and exosuit performance lags behind. In this study, three generalized methods to assess the performance characteristics of active and passive exoskeleton modes, including kinematic compliance, are introduced. The methods consisted of an isometric pull test, an isometric hold test, and an anatomical functional range of motion (FRM) test. Pilot data was captured from one subject wearing a low-cost actively and passively controlled occupational exoskeleton prototype called Robotic Exoskeleton for Upper Extremity Strength Augmentation (REUESA). Comparison of data between assessment measurements taken with and without the use of the REUESA system showed reductions in surface electromyographic (sEMG) muscle activity levels and reductions in FRMs. The experimental assessment methodology introduced in this paper may provide a platform for the ongoing development and improvement of standardized assessment methods for exoskeleton and exosuits, especially within the efforts of ASTM International Standards Committee F48.